Antropologi Untuk Pengkaji Hadis Implementasi Integrasi Ilmu Hadis dan Antropologi Pada Perguruan Tinggi Keagamaan Islam - Alfian Febriyanto; Bambang Ekanara (Jurnal Studi Hadis Nusantara, 2020)
This article discusses the integration of hadith and anthropology through the implementation of online lectures on anthropology courses at the Department of Hadith Studies at Institut Agama Islam Negeri (IAIN) Syekh Nurjati. The formulation of the research problem in this article is the implementation of the integration of the hadith studies and anthropology as well as the implementation of online lectures on anthropology courses in the Department of Hadith Studies. The research objective is to look at the implementation of the integration of the two studies and discuss the implementation of online lectures in the anthropology course. The research design used quantitative methods. The results showed that the implementation of the integration of hadith and anthropology was demonstrated through the inclusion of anthropology courses in the curriculum of the Department of Hadith Studies. Seven benefits of integrating anthropology and hadith studies 1) Anthropology helps hadith scholars in understanding the sociocultural community; 2) help understand the hadith to be applied in society; 3) help analyze the hadith that is preserved in the community; 4) helping hadith scholars understand the life around them; 5) help hadith scholars examine socio-religious phenomena/symptoms; 6) help contextualize the hadith in line with the dynamics of community life; 7) help hadith scholars carry out the spread of religion in society. Hadith studies students prefer anthropology courses to be conducted offline. Barriers to online lectures such as absence of quotas and internet signal, decreased focus of lectures, low understanding of material, unfamiliar anthropological terms, difficulty finding references. Ease of online lectures such as easy access to the internet, selection of online learning media that are internet quota friendly, giving and explaining material by lecturers. Whatsapp is the most preferred Jurnal Studi Hadis Nusantara Alfian Febriyanto, Bambang Ekanara 125 Vol 2, No 2, Desember 2020 Antropologi Untuk Pengkaji Hadis: Implementasi Integrasi Ilmu Hadis dan Antropologi Pada Perguruan Tinggi Keagamaan Islam online learning media with a percentage of 80.6%, while Zoom Meeting is the least preferred. Recorded 77.4% of the students did not like it. The majority of hadith science students were satisfied with the implementation of online lectures in anthropology courses during the Covid-19 pandemic. Keywords: Integration of Science, Anthropology, Hadith, Living Hadith, Anthropology of Hadith